Automated car safety enhancement system - Ooi, Hooi Shih
The main objective of this project is to develop a prototype model for the rapid prototyping and testing the system. In this project, it was divided into two parts which involve hardware and software environment for both parts. The first part is called as Intelligent Night-time Alert System (iNAS), while the second part is called as Intelligent Third Brake System (iTBS).